Transformasi Digital di Dunia Pendidikan: Implementasi dan Dampak Teknologi Pembelajaran - Laila, Dian; Izzatul, Ruhil; Miftah, Miftah (Journal of Science and Technology: Alpha, 2025)
The digital transformation in education has become a key pillar in addressing the challenges of 21st-century learning. The integration of educational technologies such as Learning Management Systems (LMS), online learning applications, artificial intelligence (AI), as well as virtual and augmented reality (VR/AR), has fundamentally reshaped teaching and learning paradigms across various educational levels. This study aims to analyze the implementation of digital technologies in educational settings and examine their impact on the effectiveness of the teaching and learning process. The research employs a literature review and surveys conducted among educators and students across several educational institutions in Indonesia. The findings indicate that the use of educational technologies significantly enhances student engagement, broadens access to learning resources, and enables more personalized and adaptive learning approaches. However, this transformation also faces several challenges, including limited infrastructure, the readiness of human resources, and the digital divide across regions. Therefore, a comprehensive strategy involving the government, educational institutions, and other stakeholders is necessary to ensure equitable and sustainable digital transformation in education. This study provides strategic recommendations for policy development and the enhancement of digital capacity within the national education sector.